1984
DOI: 10.1007/bf00217848
|View full text |Cite
|
Sign up to set email alerts
|

Substance P-immunoreactive sensory nerves in the lower respiratory tract of various mammals including man

Abstract: The occurrence and origin of substance P (SP)-immunoreactive (IR) nerves in the lower respiratory tract was studied by means of immunohistochemistry in the guinea-pig, rat, cat and man. In addition, biopsies from human material were also analysed by radioimmunoassay. SP-IR nerves were seen in four principal locations: 1) under or within the lining epithelium, 2) around blood vessels, 3) within the bronchial smooth muscle layer, and 4) around local tracheobronchial ganglion cells. Ligation experiments combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
233
1
6

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(247 citation statements)
references
References 37 publications
7
233
1
6
Order By: Relevance
“…Substance P-like immunoreactive afferent nerves occur in the lower respiratory tract of guinea-pig, rat, mouse, cat, man, rabbit (Wharton et al, 1979;Laitinen et al, 1983;Lundberg et al, 1984) and dog (L.A. Laitinen, A. Laitinen and J.G. Widdicombe, unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…Substance P-like immunoreactive afferent nerves occur in the lower respiratory tract of guinea-pig, rat, mouse, cat, man, rabbit (Wharton et al, 1979;Laitinen et al, 1983;Lundberg et al, 1984) and dog (L.A. Laitinen, A. Laitinen and J.G. Widdicombe, unpublished observations).…”
Section: Discussionmentioning
confidence: 98%
“…Substance P (SP) is a potent neuropeptide present in airway sensory nerves of several species including guinea-pigs and man, and found in close relation to the airway smooth muscle, beneath and within the epithelium, around ganglion cells and around blood vessels in the airway interstitium (Lundberg et al, 1984b). SP is a potent mediator of smooth muscle contraction, mucus secretion and microvascular leakage in airways of several species (Lundberg et al, 1983;1984a;Coles et al, 1984;Lotvall et al, 1989), and has been implicated in the pathogenesis of asthma (Barnes, 1986) and in bronchial hyperreactivity induced by respiratory viral infections (McDonald, 1988) or toluene diisocyanate (Sheppard & Scypinski, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…SP is present in afferent nerves in the airways of several species, including guinea-pigs and man (Nilsson et al, 1977;Lundberg et al, 1984;Polak & Bloom, 1986) and SP-immunoreactive neurones have been identified in the vagus nerve (Gamse et al, 1979). SP and other tachykinins have been shown to cause contraction of human and guinea-pig airways in vitro (Mizrahi et al, 1982;Lundberg et al, 1983) and in vivo (Andersson & Persson, 1977;Goel & Biggs, 1986).…”
Section: Introductionmentioning
confidence: 99%